2023
DOI: 10.1021/acsomega.2c07458
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Incorporated Nanofibers for Immunosensor Preparation against CD36

Abstract: The increased serum concentration of CD36 is significantly associated with atherosclerosis, insulin resistance, and diabetes mellitus. Currently, there is no sensor system used for the detection of CD36 in the clinical field. Therefore, there is a need to develop a sensor system for the detection of CD36. The large surface area/volume ratio and controllable surface conformation of electrospun nanofibers (ENs) make them highly attractive for immunosensor applications. In the present study, PS/MWCNT-PAMAM ENs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…They reported that the linear determination range of this system was 5 to 40 ng/mL and the detection limit was 3.94 ng/mL. 67 As seen in the literature, biosensor systems developed with ESNFs-CNTs nanocomposites have been reported to provide good stability and high electron transfer capability. This suggests that biosensor systems developed based on small ESFNs-CNTs have promising potential for the detection of many analytes.…”
Section: Carbon Nanotube Incorporated Esnfsmentioning
confidence: 67%
See 1 more Smart Citation
“…They reported that the linear determination range of this system was 5 to 40 ng/mL and the detection limit was 3.94 ng/mL. 67 As seen in the literature, biosensor systems developed with ESNFs-CNTs nanocomposites have been reported to provide good stability and high electron transfer capability. This suggests that biosensor systems developed based on small ESFNs-CNTs have promising potential for the detection of many analytes.…”
Section: Carbon Nanotube Incorporated Esnfsmentioning
confidence: 67%
“…They tested the applicability of the PS/MWCNT-PAMAM they developed in the electrochemical biosensor system for CD36 determination. They reported that the linear determination range of this system was 5 to 40 ng/mL and the detection limit was 3.94 ng/mL Table offers a concise and informative summary of recently developed biosensor systems based on ESNFs-CNTs.…”
Section: Electrospun Nanofibers (Esnfs)mentioning
confidence: 89%
“…The impact on solvent-type PS nanofibers is considerable. Consequently, numerous solvents, including 1,2-dichloroethane, N,N-DMF, ethyl acetate, methyl ethyl ketone, tetrahydrofuran (THF), and even limonene, were studied for the electrospinning of PS [43][44][45]. Because of its higher boiling point, conductivity, and dielectric constant compared with other solvents, the widely used DMF was the most favored solvent for the synthesis of homogenous PS nanofibers with a smooth surface [46][47][48].…”
Section: Characterization Of the Ps/mmt-pamamg3 Electrospun Nanofibersmentioning
confidence: 99%
“…The current increased af-ter the covalent immobilization of Anti-SAA on PS/MMT-PAMAM G3 . Because antigenbinding fragments (Fab) 2 are generally positively charged in the PBS medium at pH 7.4, electrostatic attraction occurred between K 3 [Fe(CN) 6 ] and the PS/MMT-PAMAM G3 /Anti-SAA-modified GCE, which caused an increased electron-transfer rate resulting in a higher electrochemical current [43]. The decrease in current was observed with the binding of SAA to the PS/MMT-PAMAM G3 /Anti-SAA-modified GCE surface.…”
Section: Characterization Of the Ps/mmt-pamam G3 /Anti-saa Immunosensormentioning
confidence: 99%
“…Biopolymer surfaces stabilize fragile biomolecules while allowing molecular access. Future work may develop multiplexed detection of pathogen/toxin panels or optimization of the Optifin Reader for future personalized rapid diagnostics [142][143][144][145][146][147]. Overall, these green recognition interfaces coupled with miniaturized electronics offer biocompatible, integrated immunosensor systems for applications in point-of-care testing through portable device formats.…”
Section: Immunosensorsmentioning
confidence: 99%